Acidophilic heterotrophs: basic aspects and technological applications - González, Ernesto; Vera, Fernando; Scott, Felipe; Guerrero, Cecilia; Bolívar, Juan M.; Aroca, Germán; Muñoz, Jesús Ángel; Ladero, Miguel; Santos, Victoria E. (Frontiers in Microbiology, 2024)
Acidophiles comprise a group of microorganisms adapted to live in acidic environments. Despite acidophiles are usually associated with an autotrophic metabolism, more than 80 microorganisms capable of utilizing organic matter have been isolated from natural and man-made environments. The ability to reduce soluble and insoluble iron compounds has been described for many of these species and may be harnessed to develop new or improved mining processes when oxidative bioleaching is ineffective. Similarly, as these microorganisms grow in highly acidic media and the chances of contamination are reduced by the low pH, they may be employed to implement robust fermentation processes. By conducting an extensive literature review, this work presents an updated view of basic aspects and technological applications in biomining, bioremediation, fermentation processes aimed at biopolymers production, microbial electrochemical systems, and the potential use of extremozymes.